2019
DOI: 10.1021/acsaem.9b01995
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2 Reduction over Rose’s Metal in the Presence of an Imidazolium Ionic Liquid Electrolyte

Abstract: The electrochemical reduction of CO 2 into reduced carbon compounds is a compelling strategy to sustainably synthesize fuels and commodity chemicals using renewable energy sources. Although promising post-transition metal electrocatalysts have been developed from monometallic thin films, limited effort has been dedicated to the use of trimetallic alloys for CO 2 electrocatalysis. In this work, we have explored the electrocatalytic effect of alloying Sn, Pb, and Bi, which are all reported as being individually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Other reports have explored the activity of alternative catalysts and produced interesting information, despite occasional claims of low overpotential based on flawed reasoning. For example: MoS2 and Nb-doped MoS2 show a higher turnover frequency for CO than Ag nanoparticles in an imidazolium RTIL-water mixture [8,9]; Sun et al [10] [12]; and Grills et al [13] employed a homogeneous Re catalyst and achieved a faradaic efficiency of 88 ± 10% in conversion of CO2 to CO. In summary, there has been considerable effort testing different materials and conditions.…”
Section: Low Overpotentialsmentioning
confidence: 99%
“…Other reports have explored the activity of alternative catalysts and produced interesting information, despite occasional claims of low overpotential based on flawed reasoning. For example: MoS2 and Nb-doped MoS2 show a higher turnover frequency for CO than Ag nanoparticles in an imidazolium RTIL-water mixture [8,9]; Sun et al [10] [12]; and Grills et al [13] employed a homogeneous Re catalyst and achieved a faradaic efficiency of 88 ± 10% in conversion of CO2 to CO. In summary, there has been considerable effort testing different materials and conditions.…”
Section: Low Overpotentialsmentioning
confidence: 99%
“…Over the past several years, our lab has developed strategies for using imidazolium ([Im] + ) based cations to promote CO2RR in non-aqueous electrolyte solutions in combination with relatively inexpensive post-transition metal-based thin film cathodes. 13,14,15 We have demonstrated that the addition of millimolar concentrations of [Im] + promoters facilitates CO2 reduction to CO at low overpotential, with selectivity exceeding FECO = 85%. By comparing the activity of monometallic thin films to their alloyed counterparts under similar electrochemical conditions, we have demonstrated that the [Im] + promoter appears to account for the high CO selectivity and functions in conjunction with the cathode material to determine the CO2RR onset potential and the electrode kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the activity of monometallic thin films to their alloyed counterparts under similar electrochemical conditions, we have demonstrated that the [Im] + promoter appears to account for the high CO selectivity and functions in conjunction with the cathode material to determine the CO2RR onset potential and the electrode kinetics. 15 Similar to controlling the pH of aqueous electrolyte solutions, use of protic organic cations or ionic liquids that are more acidic than [Im] + derivatives represent an intriguing class of ionic salts for electrochemical applications. 16,17 It has been established that the electrolyte composition can strongly influence the outcome and characteristics of electrochemical reactions such as CO2 reduction, and provide a means to tune the energetics of CO2RR reaction pathways and products distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, our lab has developed strategies for using imidazolium ([Im] + )-based cations to promote CO 2 RR in nonaqueous electrolyte solutions in combination with relatively inexpensive post-transition metal-based thin-film cathodes. We have demonstrated that the addition of millimolar concentrations of [Im] + promoters facilitates CO 2 reduction to CO at low overpotential, with selectivity exceeding FE CO = 85%. By comparing the activity of monometallic thin films to their alloyed counterparts under similar electrochemical conditions, we have demonstrated that the [Im] + promoter appears to account for the high CO selectivity and functions in conjunction with the cathode material to determine the CO 2 RR onset potential and the electrode kinetics …”
Section: Introductionmentioning
confidence: 99%
“…By comparing the activity of monometallic thin films to their alloyed counterparts under similar electrochemical conditions, we have demonstrated that the [Im] + promoter appears to account for the high CO selectivity and functions in conjunction with the cathode material to determine the CO 2 RR onset potential and the electrode kinetics. 15 Similar to controlling the pH of aqueous electrolyte solutions, the use of protic organic cations or ionic liquids that are more acidic than [Im] + derivatives represent an intriguing class of ionic salts for electrochemical applications. 16,17 It has been established that the electrolyte composition can strongly influence the outcome and characteristics of electrochemical reactions such as CO 2 reduction and provide a means to tune the energetics of CO 2 RR reaction pathways and product distributions.…”
Section: ■ Introductionmentioning
confidence: 99%